Occurrence of antimicrobial resistance in the environment in Germany, Austria, and Switzerland: a narrative review of existing evidence - Treskova, Marina; Kuhlmann, Alexander; Freise, Fritjof; Kreienbrock, Lothar; Brogden, Sandra (Microorganisms, 2022)
(1) Background: This study summarizes the current research on antibiotic resistance (AR) in the environment conducted in Austria, Germany, and Switzerland; (2) Methods: A narrative systematic literature review of epidemiological studies based on searches in EMBASE and CAB abstracts (up to 16 June2021) was conducted. Environmental reservoirs included water sources, wastewater, animal husbandry, wildlife, soil, and sediment; (3) Results: Four hundred and four records were screened, and 52 studies were included. Thirteen studies examined aquatic environments, and eleven investigated wastewater. Eight studies investigated both wildlife and animal husbandry. Less evidence was available for sediments, soil, and air. Considerable heterogeneity in research focus, study design, sampling, and measurement of resistance was observed. Resistance to all categories of antimicrobials in the WHO CIA list was identified. Resistance to critically important and highly important substances was reported most frequently; (4) Conclusions: The current research scope presents data-gathering efforts. Usage of a unified protocol for isolate collection, selecting sampling sites, and susceptibility testing is required to provide results that can be compared between the studies and reservoirs. Epidemiological, environmental, and ecological factors should be considered in surveys of the environmental dissemination of AR. Systematic epidemiological studies investigating AR at the interface of human, animal, and environmental health are needed.
Gesehen am 23.05.2022